Functionality, Limitation, and Future of Homestays in Kampung Adat Wologai - Yulius, Kevin Gustian; Sianipar, Rosianna; Pramono, Rudy (Gadjah Mada Journal of Tourism Studies, 2025)
This study explores the cultural and spatial limitations surrounding the use of traditional houses (Sa’o) as tourist accommodations in Kampung Adat Wologai, a cultural village in Ende Regency, East Nusa Tenggara, Indonesia. While rural tourism and desa wisata development often promote homestays in vernacular architecture, the sacred function of the Sa’o renders such usage inappropriate in Wologai. Using a qualitative case study approach, this research draws on field observations, semi-structured interviews with key stakeholders—including Mosalaki, village officials, tourism groups, and the local tourism office—and secondary data from academic and government sources. The findings reveal that the Sa’o are central to ancestral rituals and cannot be opened to outsiders for overnight stays. In response, the Dinas Pariwisata proposed a terminological and spatial distinction between rumah adat and rumah tradisional to guide future accommodation planning. A SWOT and SOAR analysis shows potential for homestay development through modern houses located outside the ritual core, reflecting cultural respect while meeting tourism demands. This research highlights the need for localized policy approaches and the vital role of customary leadership in sustainable tourism planning. Theoretically, it contributes to the discourse on heritage and tourism, while practically, it offers a culturally sensitive model for accommodation development in desa wisata with strong ritual traditions.